A strategy to gradual implementation of data interoperability - Gonçalves, J. B.; Domingues, L. (Electronic Government and the Information Systems Perspective. EGOVIS 2016. Lecture Notes in Computer Science, 2016)
Data interoperability is a major concern on e-government, both from the point of view of service offering and from the point of view of public administration efficiency. This paper purposes an incremental, pragmatic approach to data interoperability. It is argued that integration with minor required initial efforts from institutions is feasible, may provide useful solutions and is a solid ground basis for subsequent evolution. This paper presents general guidelines and model solutions to support this approach. Also, presents a demo implementation that proves feasibility of the purposed models and delivers useful solutions on a specific business e-government scenario. Although still limited in range and demonstrated on a quite specific business environment, it is expected that the analysis and the proposed strategies, solutions and models be of interest on a larger spectrum of data interoperability problems.